Effect of Dietary Treatments of Ascorbic Acid on the Blood Parameters, Egg Production and Quality in Quail (Coturnix coturnix japonicaM) Subjected to Heat Stress - Usman, B.A.; Mani, A.U.; Muyiwa, O.B. (International Journal of Poultry Science, 2008)
A study to determine the effects of dietary supplementation with ascorbic acid on blood parameters, egg production and quality in quail (Coturnix coturnix japonica)subjected to heat stress was conducted. Forty eight adult female quail were divided into 6 equal groups (A to F) and fed ad-libitum on either commercial layers mash ration (Groups A and D), layers mash supplemented with 200mg (Groups B and E) or 1000mg per kilogram ascorbic acid (Groups C and F). From the day treatment with Ascorbic acid started, Groups A, B and C were exposed to high temperature of about 38 °C for about 8 hours a day for two weeks. Daily feed and water consumption, egg production and quality and blood parameters were measured. By the end of the second week, feed consumption was higher in groups that were not subjected to heat stress (Groups D, E and F) than in those subjected to heat stress (Groups A, B and C). There was however no significant difference in feed consumption between birds treated with the two levels of ascorbic acid (AA) and those that were not, in both heat stressed and non stressed groups. Birds in heat stressed groups given ascorbic acid supplementation consumed more water than those not given any ascorbic acid. There was also no significant difference in weight of birds, egg production and egg weight between the groups except in birds that were not heat stressed and treated with 1000g ascorbic acid whose eggs were significantly heavier (P < 0.05). No significant difference was also observed in the mean egg weight between quail that were neither exposed to high temperatures nor treated with AA (Group D) and those that were exposed to high temperatures only (Group A), treated with AA only (Groups E and F) and exposed to high temperatures and treated with AA (Groups B and C). Following one week of the experiment, birds that were not exposed to heat stress but treated with 1000mg of AA (Group F) had heavier eggs (P< 0.05) than those that were heat stressed and given no AA (Group A) (P< 0.05) and those that were heat stressed and given 200mg AA (Group B) (P< 0.05). After 2 weeks of experiment however, eggs from birds in Groups E and F were significantly heavier (P< 0.01; P< 0.001) than those from Group A. Birds exposed to heat stress and given 1000mg AA (Group C) had heavier eggs (P< 0.05) than those also exposed to heat stress but were not given AA (Group A). The eggs of birds exposed to heat stress and not given AA (Group A) were also significantly lighter (P< 0.05) than those also not given AA but not expose to heat stress (Group D). Birds on heat stress given 200mg AA similarly had lighter eggs(P< 0.05) than those given the same level of AA but not heat stressed (Group E). There were no significant differences in the length and width of quail eggs between any of the six groups. Mean shell weight and thickness of quail eggs were however higher in birds given AA than in those not given but the differences were not significant except between birds in Group F and those in Group A (P< 0.01) and Group B (P< 0.01), respectively. No significant difference in internal egg quality as measured by Haugh unit was observed between any of the groups of the six groups. There was also no significant difference between any of the six groups in RBC count, Hb concentration, PCV%, MCV MCH, MCHC and WBC count except for a higher WBC count in Group F compared to Group A (P< 0.05). It was concluded that the quail appear to exhibit some level of heat resistance compared with other species of birds and also to benefit from ascorbic acid supplementation under hot environments; however, further studies would need to be undertaken.